Study of trade obstacles of the Association of Caribbean States (ACS Port of SpainTT, 1999)
Presents an analysis of the influence of the foreign sector, the main trading tendencies of the ACS countries, trade flows among the countries and the weight of tourism in the balance of payments. Analyzes the objectives of trade policy for each of the trading blocs, as well as the agreements on liberalization in the trading of goods within integration trading schemes. Reviews the main obstacles to trade among the ACS countries such as tariff measures, preferential duties and tariff quotas. Deals with non-tariff quotas and with non-tariff measures, investment and export financing policy.
Bibliography: p. 247-253